50-12x+8=6(8-2x)

Simple and best practice solution for 50-12x+8=6(8-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50-12x+8=6(8-2x) equation:



50-12x+8=6(8-2x)
We move all terms to the left:
50-12x+8-(6(8-2x))=0
We add all the numbers together, and all the variables
-12x-(6(-2x+8))+50+8=0
We add all the numbers together, and all the variables
-12x-(6(-2x+8))+58=0
We calculate terms in parentheses: -(6(-2x+8)), so:
6(-2x+8)
We multiply parentheses
-12x+48
Back to the equation:
-(-12x+48)
We get rid of parentheses
-12x+12x-48+58=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation

See similar equations:

| 10y-(2y-8)=40 | | 1+2p=-8-5p-6p | | 19+x/2+3/2-14=1 | | 0.13(y-2)+0.21y=0.04y-0.20 | | 3y+2=30 | | 5-5x=3(1-x) | | 3x+5=8x+11 | | 4m-2=2m+3 | | x/1-x=7/5 | | -36(-4/9c+5/12)=16c-15 | | 2x+(79-3x)+4(79-3x)+79-x=180 | | 8w-2=18 | | 0.10(y-6)+0.44y=0.04y-0.40 | | (W^2-10w+21)(2w+16)=0 | | 4/3=2/3(t+7/3) | | 2x^2-8x+16=20 | | 6+4(x-7)=4x-22 | | 88=8k | | 3|x+13|-19=-4 | | 12500=3,4*4,85*(x) | | 2x-11=3x+3 | | 2(4-x)=0 | | 5/x+4=6/11 | | -15p+11=-139 | | k+43=-34 | | 4x+3=8x+6/2 | | 7+w/2=-1 | | x-12x+23x+1=0 | | -k/4=-4 | | 3x-5(x-4)=-8+3x-12 | | 12500=3,4*4,85*x | | 1/7=4y |

Equations solver categories